Cinema e saturação mediática: o papel do documentário na vida contemporânea - Araújo, Iralene Silva (2008)
This Master s dissertation discusses the cultural role of documentary films in contemporary society, characterized by an overwhelming number of symbolic goods in various mediatic devices and supports. The hypothesis formulated here considers that the augmented supply of these goods has not come with an equivalent optimization of the quality of representations and conditions of access to disseminated contents. This leads to a form of sociocultural exclusion of the spectator who, unfamiliar with more complex productions or confused in front of the screen, finds it difficult to reflect on the meaning of the representations in circulation and to transit safely through this cultural context on an equal footing with whose who have access to and mastery over current codes and conventions. This situation leads to the following question: what qualities does the documentary film encompass and what cultural role does it effectively play amid today s mediatic saturation? Based on a research methodology underpinned by bibliographic reviews, theoretical and epistemological reflections, and analyses of documentaries, the proposed question presupposes an understanding of the sociocultural statute of the fruition of the aforementioned cinematographic genre. The answers to it are given in the light of philosophy (Arthur Schopenhauer, Ernst Fischer and Olgária Matos), of a critique of the communications media (John B. Thompson, Nestor Garcia Canclini and Paul Virilio), of semiotics (Charles S. Peirce), of etiology (Boris Cyrulnik), and of cinema theory (Sergei Eisenstein, Jacques Aumont and Bill Nichols), among other references. This theoretical picture enables us to see the documentary film as a medium and an art, with an attractive narrative that mobilizes cognitive articulations and critical formulations for the spectator